Kemampuan Penalaran Ilmiah dan Sikap Ilmiah Siswa dalam Pembelajaran Fisika Menggunakan Model Inkuiri Terbimbing dengan Peta Vee - Lintang Pascaeka; Singgih Bektiarso; Alex Harijanto (Postgraduate, University of Mataram, 2023)
This study aims to examine the effect of guided inquiry learning model with vee map on scientific reasoning skills and to examine the effect of guided inquiry learning model with vee map on scientific attitude of high school students on temperature and heat material. This type of research uses true-experiment with pretest-posttest control group design. The sample determination used cluster random sampling method. The samples of this study were XI MIPA 1 class as the control class and XI MIPA 2 as the experimental class. The research instruments used were pre-test and post-test questions using Lawson Classroom Test Scientific Reasoning indicators and scientific attitude questionnaires. Data analysis techniques using SPSS 26. The results showed that there was a significant effect of guided inquiry learning model with vee map on scientific reasoning skills with a significance of 0.000 and there was a significant effect of guided inquiry learning model with vee map on the scientific attitude of students with a significance of 0.000. Therefore it can be concluded that inquiry learning model accompanied by vee map can encourage students to be active in concept discovery and improve students' scientific reasoning skills.